We shall not be moved : How Liverpool's working class fought redundancies, closures and cuts in the age of Thatcher - Marren, Brian (Book collections on Project MUSE., 2016)
The city of Liverpool had frequently been prone to industrial unrest for most of its recent history, but it was the dawn of Thatcher and the sanctioning of neoliberal economic strategies which made Liverpool a nucleus of resistance against the encroaching tide of right-wing politics and sweeping de-industrialisation. This critique explores six case studies which will illustrate how elements of a highly politicised local working-class fought against the rapid rise in forced redundancies and industrial closures.